Advancing Agricultural Biotechnology in Israel - Chalutz, E.; Galun, E.; Harel, S. (International Service for National Agricultural Research, 2001)
The total land area of Israel is about 20,000 km2, about 2% of the area of Egypt. Precipitation ranges from about 900 mm in the hilly north to almost nil in the desert south. About 5,000 km2 are cultivated, half of this under irrigation. Water supply is scarce, about 1.5 billion m3 annually, while more water is actually being used in recent years, causing a water deficit — lowering the level of ground water. The supply of water is regulated by a national authority, and no individual can make free use of water even from private wells. An increasing percentage of water is recycled from urban areas, and used to irrigate certain crops such as cotton. While, overall, agriculture produces more than its own needs (in monetary values), most of its major commodities are imported. Agricultural exports include flowers, citrus, vegetables and cotton fibers. Agricultural exports exceed US$ 1 billion annually and comprise more than 5% of total exports.